2020
DOI: 10.21203/rs.3.rs-122352/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative Evaluation of SARS-CoV-2 Inactivation Using a Deep Ultraviolet Light-Emitting Diode

Abstract: Inactivation technology for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is certainly a critical measure to mitigate the spread of coronavirus disease 2019 (COVID-19). A deep ultraviolet light-emitting diode (DUV-LED) would be a promising candidate to inactivate SARS-CoV-2, based on the well-known antiviral effects of DUV on microorganisms and viruses. However, due to variations in the inactivation effects across different viruses, quantitative evaluations of the inactivation profile of SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…It also indicates that the AlN layer has no effect on the peak emission wavelength. It is worth noting that the minute blue shift in LED NIII (0.057 nm) is due to the lowering of quantum confinement stark effect (QCSE) due to lower electrostatic field at the interface of LQB and EBL [8]. The emission spectra of LED B impressively enhanced as compared to LED A.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It also indicates that the AlN layer has no effect on the peak emission wavelength. It is worth noting that the minute blue shift in LED NIII (0.057 nm) is due to the lowering of quantum confinement stark effect (QCSE) due to lower electrostatic field at the interface of LQB and EBL [8]. The emission spectra of LED B impressively enhanced as compared to LED A.…”
Section: Resultsmentioning
confidence: 97%
“…In spite of many efforts, the carrier leakage is still a headache for the researcher and the main barrier in the development of efficient UV LEDs, especially DUV LEDs. Inspired by the valuable features, of AlGaN-based DUV (222 nm) recently many researcher reported for the disinfection of SARS-2 (COVID-19) [1,8]. Interestingly, the optoelectronic performance of this specific LED (222 nm) is not satisfactory.…”
Section: Introduction Iii-nitridementioning
confidence: 99%
“…Under these circumstances and compared with the experiment on glass in the dark, we may confirm that the intensity of UVA radiation at the range of 315-400 nm is not strong enough to deactivate SARS-CoV-2 effectively. Several reports investigated the inactivation of SARS-CoV-2 by direct deep UV irradiation [42][43][44]. Heilingloh et al [45] reported that SARS-CoV-2 was very susceptible to UVC irradiation, while a low inactivation was found under UVA.…”
Section: Antiviral Resultsmentioning
confidence: 99%
“…Reports have confirmed the use of UVC LEDs generating around 250-300 nm wavelength to effectively inactivate microorganisms, including bacteria and surrogates [11], viruses and fungi [17]. Although studies agree that shorter wavelengths are more effective at disinfecting coronaviruses [18], there is a dearth of knowledge specifically on effects of wavelengths on SARS-CoV-2 disinfection as relates to dose and irradiation time. Ideally, a test using a consistent set of LED sources at varying wavelengths on actual SARS-CoV-2 should be performed.…”
Section: Resultsmentioning
confidence: 99%